ANGPTL4 in gestational diabetes: a diagnostic biomarker linked to placental senescence - Yu-Feng He; Hui Chen; Chuan-Meng Zhang; Su-Su Yang; Xiao-Long Yang; Li-Shuai Jiang; Fan Wang; Shu-Guang Zhou (Functional & Integrative Genomics, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Self-healing materials for food packaging: Design principles, activation mechanisms and implications for food safety - Mengzi Nie; Runkang Qiu; Huihui Yang; Xiangyu Liang; Ziqian Li; Long Li; Bei Fan; Li-Tao Tong; Peihua Ma; Fengzhong Wang (Food Research International, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Preparation of Ag/CuV2O6 nanowires and investigation of the delayed antibacterial effect of fluorescent materials on photocatalysts - Xu Li; Yifang Zhang; Qiao Xia; Jiye Fan; Huaxiang Lin; Rusheng Yuan; Jinlin Long (Journal of Environmental Chemical Engineering, 2026)

Smartphone-assisted fluorescence sensor based on iron-doped carbon dots for rapid detection of tert-butyl hydroquinone in edible oils - Huihui Yang; Qinghua Liu; Yuanyuan Liu; Qian Su; Yiwei Dong; Minmin Li; Bei Fan; Fengzhong Wang; Long Li (Food Chemistry, 2026)

A pH-responsive bilayer film based on PHBV/ZnO and polyvinyl alcohol/carboxymethyl konjac glucomannan/alizarin was developed for monitoring and maintaining pork freshness - Qiu-Yu Peng; Meng Wang; Song Chen; Long-Hua Zou; Yun-Cheng Li; Fan-Bing Meng (Food Chemistry, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Dopamine-induced interlayer bridging for enhanced through-plane thermal conductive performance of expanded graphite-based thermal interface materials - Yuyuan Fan; Long Gao; Jinxing Liu; Yajuan Zhong; Sufang Yang; Xueyao Feng; Hongtao Yu; Junfen Li; Xiaodong Tian; Lei Zheng; Xing Guo; Xi Yan; et al. (Chemical Engineering Journal, 2026)

Titanium isotope fractionation in hydrous and oxidized large igneous provinces - Sheng-Zhu Zhu; Xiao-Long Huang; Peng-Li He; Fan Yang; Jin-Long Ma; Yang Yu; Xin-Yue He; Le Zhang; Gang-Jian Wei (Chemical Geology, 2026)

Green and efficient maize varieties synergize global yield and nitrogen sustainability - Xun Wei; Yulong Yin; Xueqin Zhu; Ziwen Li; Zhenying Dong; Yan Long; Yanbo Wang; Jiuran Zhao; Changling Huang; Xingming Fan; Huabang Chen; Pervez H. Zaidi; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Nano-assembly of dioscin via zein–Angelica sinensis polysaccharide composite nanocarriers: structure, stability, bioaccessibility and bioactivity - Tian-Le Mao; Yue Wu; Zhi-Xin Xu; Fan Yang; Jing Li; Xin Guo; Qian-Lan Wu; Ya-Fang Shang; Kiran Thakur; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

Climatic-hydrological-geothermal coupled mechanism drives lake evolution and Li-B enrichment from mega-lakes to salt lakes on the Tibetan Plateau - Jilei Yang; Qishun Fan; Qingkuan Li; Chuanyong Ye; Hao Long; Tianyuan Chen (Earth-Science Reviews, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Experimental and numerical simulation study on failure mode transformation in deep high sidewall cavern - Fan Li; Qiangyong Zhang; Kang Duan; Gongfeng Xin; Guanxu Long (Tunnelling and Underground Space Technology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Structural analysis of protein and identification of key protein during the evolution of whole egg liquid foam - Yuanyuan Zhang; Xiang Fan; Haobo Jin; Yi Sun; Yanli Wang; Erjiao Li; Sadaqat Ali; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2026)

Trace iron-induced electron delocalization metallization on the BN surface for hyper integrated C-band wideband absorber - Hui Gao; Chunyan Ding; Junyu Shen; Guohao Wu; Mingyang Fan; Zhuoyang Li; Long Xia; Guangwu Wen; Feng Xu; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Microbe–Metabolite Interactions in Cave Soils Synergistically Regulate the Environmental Persistence of Pseudogymnoascus destructans - Denghui Wang; Fan Wang; Shaopeng Sun; Long Huang; Keping Sun; Zhongle Li; Jiang Feng (Environmental Microbiology, 2026)
Pseudogymnoascus destructans (Pd), the causative agent of bat white‐nose syndrome, persists in cave soils and acts as a chronic source of infection, yet the environmental processes governing this reservoir remain unclear. We performed seasonal sampling of bat cave soils in Northeast China and combined metagenomic, untargeted metabolomic and physicochemical analyses to identify drivers of Pd loads. Pd abundance tracked strong seasonal gradients in temperature, soil water content, electrical conductivity and nitrogen availability. The microbial community structure exhibited pronounced seasonal variation, primarily associated with pH, and was governed predominantly by stochastic ecological processes. Nitrogen‐cycling genes showed a switch from nitrogen fixation and nitrification in summer to denitrification and nitrate reduction in winter. Antibiotic resistance genes and mobile genetic elements covaried with core bacterial taxa, while antifungal metabolites such as tetracycline, glycitin and chrysin were positively associated with putatively antagonistic genera (e.g., Rhodanobacter , Pseudomonas , Streptomyces , and Bacillus ), indicating a microbe–metabolite defence network. Structural equation modelling revealed a temperature‐driven cascade linking nutrient cycling, microbial communities, metabolite profiles and Pd loads. Our results show that seasonal dynamics of Pd in cave soils emerge from interactions between climate‐regulated soil processes and microbe–metabolite feedbacks, with implications for environmental control of pathogenic fungi.

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Pore engineering and charge attenuation for covalent organic framework membranes: A new approach to high-performance molecular–ion separation - Qiao Liu; Nong Xu; Kaiming Li; Qing Wang; Long Fan; Yinhua Wan; Xiang Hu; Zhifeng Huang (Water Research, 2026)

Antifungal activity and action mechanisms of 2, 4-Di-tert-butylphenol from Bacillus amyloliquefaciens Z-7 volatile organic compounds against Verticillium dahliae - Hong Tan; Jie Zeng; Jinyi Wu; Chunsheng Wang; Lihua Zhang; Anlong Hu; Zhibo Zhao; Youhua Long; Rong Fan; Xiaoping Hu; Rongyu Li (Pesticide Biochemistry and Physiology, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

ZmSWEET6A/6B are required for maize male fertility via balancing sugar and lipid metabolism during pollen and anther development - Shuangshuang Liu; Yilin Jiang; Canfang Niu; Fan Zhang; Lina Zhao; Quancan Hou; Ziwen Li; Yingwei Qu; Bin Ma; Qingping Jiang; Yan Long; Xueli An; et al. (Science Bulletin, 2026)

Hydrothermal Nb mineralization during fenitization in the carbonatite system: Evidence from the Bayan Obo REE-Nb deposit, China - Qi Li; Jian Zhao; Xiaochun Li; Long Huang; Hongrui Fan; Yonggang Zhao; Xianhua Li; Mingguo Zhai (Journal of Asian Earth Sciences, 2026)

The introduction of impurity energy level into electrode materials to improve the performance of photo-sensitive supercapacitors - Haifeng Tan; Wanjiang Long; Weilong Li; Sushuang Feng; Chenrui Fan; Yijie Gao; Xue Yang; Zhaoyu Ren (Chemical Engineering Journal, 2026)

Propyl propionate enabling stable operation of 4.55 V LiCoO2/graphite pouch cells at various temperatures via solvation and interface modulation - Shiran Li; Yu Zhang; Xiao-Zhong Fan; Xiaomeng Wang; Gupei Ding; Weiguo Li; Xu-Feng Zang; Miaomiao Han; Long Kong (Chemical Engineering Journal, 2026)

Manipulating non-radical pathway preference in PMS-mediated phenolic degradation: Substituent-dependent catalyst-pollutant interfacial interaction over single-atom Fe-N-C - Fan Huang; Xianhu Long; Ting Li; Xuexia Guo; Lingling Hu; Huinan Zhao; Shuanghong Tian; Minhua Su; Chun He (Chemical Engineering Journal, 2026)

Downregulation of UQCRC1 Expression Leads to Cognitive Decline by Disrupting the Cilia in the Dentate Gyrus - Jing Zhang; Tianyao Liu; Zonghong Long; Zuoxi Wu; Jing Luo; Fuhai Bai; Lianyu Zhou; Hong Gong; Meifeng Gong; Hong Li; Xiaotang Fan (Neuroscience Bulletin, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

Contract coordination of coal supply chain considering reciprocity altruism under water cap-and-trading regulations - Peiyao Wang; Pu Dong; Long Zhang; Yan Li; Peishan Fan; Xiaofan Li; Chaowei Wang (Environment, Development and Sustainability, 2026)

Four new flavonoids from Sophora flavescens and their antibacterial activities - Yun Gao; Xin-Min Li; Fan-Fan Cao; Guo-Qing Long; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Thallium isotope insights into Mn Oxides as precursor to Ediacaran Mn Carbonate Ore - Xuwen Luo; Haifeng Fan; Jean Clemente; Chao Li; Hongjie Zhang; Long Chen; Yaowen Wu; Shaohong Fu; Jianfeng Gao; Hanjie Wen; Sune G. Nielsen (Geochimica et Cosmochimica Acta, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Regulation mechanism of fatty acid chain length and saturation on lipid adsorption behavior and protein conformation during whole egg liquid foam evolution - Yuanyuan Zhang; Yanli Wang; Haobo Jin; Yi Sun; Sadaqat Ali; Erjiao Li; Xiang Fan; Yanbin Song; Yunxin Sun; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2026)

Synergistic regulation of pore structure and surface charge in COF-based membranes for monovalent ion sieving - Long Li; Qian Cao; Renzhong Wang; Ying Li; Yang Zhao; Yiqun Fan; Zhaohua Li; Feng Shao (Desalination, 2026)

Horizontal evolution characteristics of near-inertial sea surface currents induced by the tropical cyclones in the Guangdong-Hong Kong-Macao Greater Bay area - Lei Ren; Hexu Wang; Beinuo Zhou; Xiaofan Lou; Zhenglin Li; Long Bai; Fan Yang; Zhenchang Zhu; Fearghal O'Donncha; Jun Wei; Michael Hartnet (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Host size and parasite density impact on the efficacy and reproductive output of Pyemotes zhonghuajia, a biological control agent of potato tuber moth - Chenming Xiao; Xiong Zhao He; Xuelin Li; Di Fan; Long Zhang; Chengxu Wu; Maofa Yang; Jifeng Hu; Guy Smagghe; Jianfeng Liu; Fangling Xu (Experimental and Applied Acarology, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Dissecting the aberrant vasculature of glioblastoma: mechanisms and therapeutic targets - Yinan Li; Yinfei Du; Fan Guan; Xuetong Li; Shu Cui; Wei Gao; Xinmiao Long; Minghua Wu (Cancer and Metastasis Reviews, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Study on structure regulation of porous carbon prepared from phenol/ammonium components of semi-coking wastewater - Xianjie Wang; Long Yan; Yufei Wang; Shuaige Shi; Jian Li; Xiaoyong Fan (Fuel, 2026)

Selective hydrogenation of nitriles to primary and secondary amines via Ni0/Ni2+ dual sites - Tongtong Fan; Jiaheng Qin; He Wen; Siyu Li; Hong Zhao; Tong Li; Xiao Zhang; Jiantai Ma; Yu Long (Fuel, 2026)

Interfacial reorganization of egg yolk granules by ultrasound-assisted pH-shifting: concentration-dependent lecithin functionality from emulsion stabilizer to competitive displacer - Shuangshuang Li; Yaqin Yang; Yi Sun; Yuanyuan Zhang; Xiang Fan; Mohamed Salama; Guofeng Jin; Long Sheng (Food Chemistry, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Interface passivation with 1,3-propyldiammonium diiodide enables production-line compatible perovskite/silicon tandem solar cells - Dongyong Fan; Longhao Jisi; Wenfeng Zhang; Xin Hu; Fang Wen; Wei Long; Yuchao Hu; Yifeng Zhang; Guoqiang Xing; Liping Su; Haijin Li; Wenhua Zhang; et al. (Chemical Engineering Journal, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Corrigendum to “Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea” [Lithos 512–513(2025) 108151] - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2026)

Recovering residual carbon from coal gasification slag via flotation for wastewater treatment - Haiyu Wang; Jufen Zhu; Qi Yan; Jiale Wen; Junfei Shang; Xiaoyong Fan; Baoning Li; Fanhui Guo; Qingbo Wei; Lingxing Zan; Yuxuan Liu; Jian Li; et al. (Journal of Water Process Engineering, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Magnetic iron oxide-loaded coal-based activated carbon for Enhanced copper (II) removal: Batch and fluidized bed studies - Wen Fan; Bo Lv; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Fuel, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Experimental study on seismic performance of low-yield-point steel tubular links - Jun-Yu Wu; Liang-Dong Zhuang; Ji-Zhi Zhao; Li-Long Fan; Xiao Feizhi (Engineering Structures, 2026)

Tailored plasmonic interfaces on LAS glass-ceramic gratings for high-efficiency electromagnetic wave absorption - Chunyan Ding; Shanshan Fan; Zhengliang Qiu; Zhuoyang Li; Yiteng Zhang; Songsong Wu; Liping Tong; Bo Zhong; Long Xia; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Typhoon-induced cascade effects on hydrological and biogeochemical dynamics in estuary-coast continuum: Insights from multidisciplinary observations and model forecasting in Zhanjiang Bay, China - Huizi Long; Peng Zhang; Jibiao Zhang; Menghan Gao; Binbin Fan; Zhangxi Hu; Zhihao Li; Rong Chen (Journal of Hydrology, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Evaluation of deconvolution methods and loading parameters in nanoindentation characterization of sodium aluminosilicate hydrate gel in fly ash based geopolymers - Wenrui Xu; Youjun Xie; Fan Wang; Zhiyu Luo; Gang Ma; Yiran Li; Yingjie Li; Guangcheng Long; Zhuo Tang (Journal of Cleaner Production, 2026)

TFEB-driven autophagy enhancement via a ROS-triggered NIR-II nanoplatform for targeted non-alcoholic fatty liver disease therapy - Fan Wu; Xin Kuang; Jian Xiong; Chaoqiang Li; Jinkang Zheng; Bibo Zhao; Sanlin Deng; Gui-long Wu; Qinglai Yang; Guodong Chen (Chemical Engineering Journal, 2026)

224Ra labeled nanohydroxyapatite for targeted alpha therapy of metastatic lung cancer - Jie Lyu; Long Qiu; Fuyuan Tan; Yuying Yu; Xisheng Fan; Tianzhen Ye; Shuran Lei; Jiali Liao; Yuanyou Yang; Ning Liu; Feize Li (Chemical Engineering Journal, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

Efficient removal of microplastics through a combined treatment process: Pre-filtration and adsorption - Bo Lv; Wen Fan; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Journal of Environmental Management, 2025)

Ag2O-decorated poly(lanthanide–β-cyclodextrin) based on a silica microsphere with reversible photo-regeneration: Highly sensitive and broad-spectrum fluorescent sensing of tetracycline antibiotics - Junlong Li; Zerong Long; Jianling Wang; Tianli Fan; Laifang Qi (Journal of Environmental Chemical Engineering, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Stock Assessment Using Three Bayesian Models for Chinese Icefish in Taihu Lake, a Major Freshwater Fishery in the Yangtze River Basin, China - Zhipeng Li; Long Ren; Yingchun Fan; Dongpo Xu (Fisheries Management and Ecology, 2025)
Inland fisheries play a crucial role in global food security, particularly in low‐income regions, yet their management has often been overshadowed by a focus on marine fisheries. We investigated the resource utilization and management status of Chinese icefish ( Neosalanx tangkahkeii ) in Taihu Lake, the largest freshwater lake in East China with significant fishery resources, over 35 years prior to the implementation of a decade‐long fishing ban in 2020. Using three surplus production models (SPMs)—ASPIC, SPiCT, and JABBA—we evaluated historical biomass and fishing pressure dynamics of the Chinese icefish population. Persistent overfishing that reduced annual biomass consistently below MSY for over two decades confirmed unsustainable fishing mortality. The SPiCT model was the best fitting, but all models were reliable, with

Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Quantifying threshold water tables for the stability of the oasis-desert ecotone in arid areas - Yong Wang; Xing Li; Yong Zhao; Long Yan; Fan He; Jiaqi Zhai; Yajie Hu; Yuan Liu; Wei Deng; Zhu Wang; Qingming Wang; Minjian Chen (Journal of Environmental Management, 2025)

Spin orbit charge transfer enhances intermolecular hydrogen atom transfer catalyzed polymerization for conductive elastomers syntheses - Qingze Pan; Saran Long; Jianwei Li; Pengzhong Chen; Junhui Wang; Kaifeng Wu; Jiangli Fan; Xiaojun Peng (Chemical Engineering Journal, 2025)

Research and application mechanism of chlorination roasting for polymetallic minerals and waste - Zhi-yu Fan; Long Wang; Ren-yun Zhang; Yi-yong Wang; Ting-an Zhang; Xing-jian Wang; Ji-dong Li; Xin-xin Zhao; Wei-juan Li (Minerals Engineering, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Current status and influencing factors of blue carbon in seagrass beds: An extensive survey and comprehensive analysis in the Yellow and Bohai Seas, China - Xiang Zhao; Jie Sun; Fan Li; Shao-Wen Li; Hai-Xia Su; Xiu-Fen Ma; Lei Yang; Gui-Xiang Zheng; Wan-Long Sun; Pei-Dong Zhang (Journal of Environmental Management, 2025)

Effect of H2O physicochemical properties on NO formation mechanism in NH3 oxy-steam combustion under MILD mode - Xiaojian Zha; Zewu Zhang; Zhenghong Zhao; Long Yang; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Highly stable and active cerium single-atom immobilized Ti3C2TX MXene for high-stability lithium‑sulfur batteries - Shengdong Jing; Shilan Li; Xiaoli Peng; Long Yuan; Shengjun Lu; Yufei Zhang; Haosen Fan (Chemical Engineering Journal, 2025)

Polysaccharide nano‑selenium in the regulation of neuroinflammation: A review of mechanisms, functional potential, and activity evaluation - Xinyue Liu; Simal-Gandara Jesus; Zhiqiang Kong; Ningning Fan; Yunchong Mi; Qiong Wang; Yatao Huang; Long Li; Jia Lu; Bei Fan; Minmin Li (Carbohydrate Polymers, 2025)

PM2.5 and PM10 vertical distribution retrieval methods based on coherent Doppler lidar via machine learning: for haze and dust in Qingdao - Rongzhong Li; Kangwen Sun; Xitao Wang; Guangyao Dai; Mengqi Fan; Li Ma; Xiaowei Zheng; Wenrui Long; Fanqian Meng; Qichao Wang; Songhua Wu (Atmospheric Environment, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Specific catalytic hydrogenation of 2-butyne-1,4-diol to butane-1,4-diol - Li Li; Xian-Yong Wei; Shun-Hong Lv; Xiang Bai; Yierxiati Dilixiati; Jun-Long Wang; Xiao-Yan He; Zhi-Min Zong; Xing Fan (Fuel, 2025)

Glucose membrane-assist pyrolysis engineered ultrafine FeP/CoP3-doped hollow carbon nanospheres: Enhanced bifunctional oxygen catalysts for rechargeable zinc-air batteries - Fan Li; Jilan Long; Li Kang; Fei Zhao; Simeng Ding (Chemical Engineering Journal, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Optimizing lithium recovery from artificial β-spodumene slags: A breakthrough in pyrometallurgical processing of spent lithium-ion batteries - Shiliang Chen; Xin Wang; Hu Li; Guan Xiutao; Youqi Fan; Yuchi Yan; Zhipeng Guo; Hanbing He; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Selective sulfite activation based on a non-radical reaction pathway with dominant 1O2 generation triggered by oxygen vacancies-enriched CuCo2O4 for efficient degradation of ciprofloxacin - Jinyuan Zhang; Long Cao; Jianxin Liu; Yawen Wang; Rui Li; Xiaochao Zhang; Yunfang Wang; Caimei Fan (Journal of Environmental Chemical Engineering, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Improved Biome-BGC model for simulating spatiotemporal dynamics of gross primary productivity in evergreen broadleaf forests of the karst region - Hengyuan Liu; Qian Ding; Yuechen Li; Lei Fan; Long Zhao; Mingguo Ma (Environmental Modelling & Software, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Antibacterial Activity of Essential Oils from Clove and Elsholtzia Plants Against Common Pathogens of Bovine Mastitis, Antioxidant Activity, and Toxicity to Bovine Mammary Epithelial Cells - Xu-Dong Wang; Jia-Li Bai; Zhen-Jia Ma; Jie Fan; Wei-Bao Kong; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Current Microbiology, 2025)

Research on Operational Risk for Northwest Passage Cruise Ships Using POLARIS - Long Ma; Jiemin Fan; Xiaoguang Mou; Sihan Qian; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
In the context of global warming, polar tourism is developing rapidly, and the demand for polar cruise travel in the Northwest Passage continues to increase, while sea ice has long been a key factor limiting the development of polar cruise tourism. This study focuses on the operational risk of sea ice on cruise ships in the Northwest Passage (NWP), aiming to provide a scientific basis for ensuring the safety of cruise ship navigation and promoting the sustainable development of polar tourism. Based on ice data from 2015 to 2024, this study used the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology recommended by the International Maritime Organization (IMO) to establish three scenarios for the route of ice class IC cruise ships: light ice, normal ice, and heavy ice. The navigable windows were systematically analyzed and critical waters along the route were identified. The results indicate that the navigable windows for IC ice-class cruise ships under light ice conditions are from mid-July to early December, while the navigable period under normal ice conditions is only from mid- to late September, and navigation is not possible under heavy ice conditions. The study identified Larsen Sound, Barrow Strait, Bellot Strait and Eastern Beaufort Sea as critical waters on the NWP cruise route. Among them, Larsen Sound and Eastern Beaufort Sea have a more prominent impact on voyage scheduling because their navigation weeks overlap less with other waters. This study provides a new idea for the risk assessment of polar cruise ships in ice regions. The research results can provide an important reference for the safe operation of polar cruise ships in the NWP and the decision-making of relevant parties.

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Comparative Research on Vessel Navigability on the Northern Sea Route Based on the NSR Admission Criteria and POLARIS Methodology - Long Ma; Sihan Qian; Xiaoguang Mou; Jiemin Fan; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
At present, sea ice remains a critical factor affecting the safety of vessel operations along the Northern Sea Route (NSR). However, inconsistencies between the navigability outcomes derived from the criteria for the admission of ships in the area of the Northern Sea Route (NSR criteria) and the polar operational limit assessment risk indexing system (POLARIS) methodology present challenges for navigational decision-making. This study aims to conduct a systematic comparison of the POLARIS methodology and the NSR criteria in evaluating the navigability of independently operating vessels classified as Arc4 to Arc9. Through comparative calculations of navigability and the navigability rates for six ice-class vessels across 27 districts using the two methods, this study reveals the consistencies and discrepancies in their navigability outcomes. Firstly, using the POLARIS methodology, the risk index outcome (RIO) is calculated for six ice-class vessels across 27 districts. For these districts, the navigability threshold is defined when 95% or more of the area exhibits an RIO greater than or equal to zero. Secondly, using the NSR criteria, navigability ratios for six ice-class vessels under varying ice conditions are evaluated. A navigability threshold is defined when 95% or more of the ice conditions in a district are classified as navigable. Finally, a quantitative comparison of the weekly navigability ratios obtained by the two methods is conducted to reveal the consistencies and discrepancies in the navigability outcomes of each ice-class vessel across different NSR districts. The results indicate that the consistency between the navigability outcomes of the two methods decreases with lower vessel ice classes, particularly in September and March. In general, the consistency of performance between the two methods in terms of navigability outcomes deteriorates as the vessel ice class decreases and ice conditions become more complex. This study provides a scientific foundation and data-based support for route planning and real-time decision-making in polar waters.

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Microbial mechanism of naturally formed stable partial nitrification in sequencing batch biofilm reactors - Xiao-Yan Fan; Yue Niu; Xing Li; Shen-Bin Cao; Meng-Yuan Zheng; Shi-Long Zhou (Journal of Environmental Chemical Engineering, 2025)

Revealing the potassium poisoning mechanism of V2O5-MoO3/TiO2 catalyst for chlorobenzene catalytic oxidation - Jiaying Xing; Jisheng Long; Li Bai; Guimin Wang; Yufei Fan; Haiyan Liu; Jianjun Chen; Junhua Li (Fuel, 2025)

A 7-year feed study on the long-term effects of genetically modified maize containing cry1Ab/cry2Aj and EPSPS genes on gut microbiota and metabolite profiles across two generations of cynomolgus macaques - Chenyun Wang; Shengtao Fan; Minghao Li; Yousong Ye; Zheli Li; Weihu Long; Yongjie Li; Zhangqiong Huang; Qinfang Jiang; Wanjing Yang; Rujia Yang; Donghong Tang (Food and Chemical Toxicology, 2025)

Effective collective value-added recycling of nitrate and sulfion in wastewater via synergistic electrocatalysis of dual-active sites on copper-cobalt oxides - Donglin Zhao; Song Wu; Yihan Zhang; Dongxu Cao; Ruizhi Li; Yan Long; Guangyin Fan (Chemical Engineering Journal, 2025)

ARHGAP17 Inhibits Hepatocellular Carcinoma Progression by Inactivation of Wnt/β-Catenin Signaling Pathway - Sirui Fan; Hongqing Zhao; Cheng Li; Xing Chen; Mingjie Sun; Fengyang Chen; Chao Long; Yinghui Zhou; Boyuan Nan; Hao Zhao; Wei Zhang (Biochemical Genetics, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Overview of monitoring methods and environmental distribution: Microplastics in the Indian Ocean - Long Zhou; Jingxi Li; Chang Zhao; Jiaxuan Yin; Jinfeng Ding; Wei Cao; Wei Fan (Marine Pollution Bulletin, 2025)

Accurate identification and formation mechanism unraveling of radicals in UV-induced peracetic acid activation system using in-situ electron paramagnetic resonance - Long Chen; Ruohan Zhang; Zhaoli Liu; Fan Li; Boyu Huang; Wen Liu (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effective degradation of ammonia nitrogen wastewater by novel three-dimensional residual charcoal particle electrode - Jiale Wen; Jian Li; Jufen Zhu; Haiyu Wang; Qi Yan; Luyuan Chen; Jialu Qiao; Xiaoyong Fan; Long Yan (Journal of Water Process Engineering, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Data-driven pipeline modeling for predicting unknown protein adulteration in dairy products - Huihui Yang; Yutang Wang; Jinyong Zhao; Ping Li; Zhixiang Li; Long Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2025)

Simultaneous determination of vegetable oil frying frequency and peroxide value based on the three-dimensional fluorescence spectroscopy and machine learning - Huihui Yang; Yutang Wang; Bei Fan; Qing Chen; Meifeng Wu; Fengzhong Wang; Long Li (Food Chemistry, 2025)

Nitrogenous chemical constituents and their antitumor activities evaluation in vitro from the aerial parts of Corydalis impatiens (pall.) Fisch - Ze-dong Nan; Yi-dong Zhu; Chao-fan Deng; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Natural Product Research, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Effects on extracellular and intracellular antibiotic resistance genes and their potential hosts in activated sludge under stress of high concentrations of antibiotics - Xiao-Yan Fan; Meng-Yuan Zheng; Xing Li; Shen-Bin Cao; Yue Niu; Shi-Long Zhou (Journal of Water Process Engineering, 2025)

Mechanistic insights into phenol-ammonia synergy for optimizing phenolic porous carbon synthesis and pore formation - Xianjie Wang; Long Yan; Yufei Wang; Shuaige Shi; Jian Li; Xiaoyong Fan (Fuel, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Mantle wedge serpentinites as a potential nitrogen reservoir regulating subduction-zone nitrogen recycling and mantle heterogeneity - Kan Li; Kai Wu; Amber Jie Yu; Yi-Fan Du; Weidong Sun; Long Li (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

How to restore ecology and reduce carbon emissions in abandoned mines in a safe and environmentally friendly way？ - Wei Zhao; Jingwei Huang; Kai Wang; Peifeng Hu; Yue Huang; Chengxin Li; Yuxuan Zhu; Long Fan; Lijun Zhao (Process Safety and Environmental Protection, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

U-Pb ages of apatite, sulfur isotopes of sulfides and possible origin of the Dashui hematite-rich, sulfide-deficient gold deposit in the West Qinling orogen, Central China - Liang Fan; Jia Chang; Jian-Wei Li; Ji-Xiang Sui; Shi-Guang Du; Long-Hui Huang (Journal of Asian Earth Sciences, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Enhanced visual detection of litchi fruit in complex natural environments based on unmanned aerial vehicle (UAV) remote sensing - Changjiang Liang; Juntao Liang; Weiguang Yang; Weiyi Ge; Jing Zhao; Zhaorong Li; Shudai Bai; Jiawen Fan; Yubin Lan; Yongbing Long (Precision Agriculture, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

Influence of synergistic/competitive interactions of nonionic emulsifiers and proteins on the foam stability of whole egg liquids: Based on air-water and oil-water dual interface perspectives - Yuanyuan Zhang; Haobo Jin; Yanli Wang; Erjiao Li; Sadaqat Ali; Xiang Fan; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Design, integration, and field evaluation of a selective harvesting robot for broccoli - Shuo Kang; Sifang Long; Dongfang Li; Jiali Fan; Dongdong Du; Jun Wang (Computers and Electronics in Agriculture, 2024)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Enhanced rare earth alkali cake washing and alkaline wastewater disposal via mineral phase transformation and ultrasound - Jianfei Li; Zhenhui Long; Yanglei Geng; Ruifeng Ma; Xiaowei Zhang; Yanhong Hu; Jinxiu Wu; Feng Guo; Wenbin Xin; Xiaoyan Hao; Zhicheng Dong; Fan Xiufeng (Minerals Engineering, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

Development of multifunctional fruit packaging by incorporating starch aldehyde-quercetin conjugate into chitosan coating films - Yufeng Sun; Yang Ju; Lili Wang; Ran Tao; Long Li; Bei Fan; Fengzhong Wang (Food Hydrocolloids, 2024)

Per- and polyfluoroalkyl substances (PFAS) at low concentration improve coagulation efficiency but induce higher membrane fouling in drinking water treatment - Qianyi Chen; Junling Wang; Zhaoyang Su; Long Tian; Fan Huang; Ting Liu; Nigel Graham; Guibai Li; Wenzheng Yu (Environmental Pollution, 2024)

Machine-learning downscaling of GPM satellite precipitation products in mountainous regions: A case study in Chongqing - Yushi Gan; Yuechen Li; Lihong Wang; Long Zhao; Lei Fan; Haichao Xu; Zhe Yin (Atmospheric Research, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Navigability of Liquefied Natural Gas Carriers Along the Northern Sea Route - Long Ma; Sihan Qian; Haihui Dong; Jiemin Fan; Jin Xu; Liang Cao; Shuai Xu; Xiaowen Li; Chengcheng Cai; Yuanyuan Huang; Min Cheng (Journal of Marine Science and Engineering, 2024)
As Arctic sea ice continues to melt and global demand for clean energy rises, Russia’s Liquefied Natural Gas (LNG) exports via the Northern Sea Route (NSR) are rapidly increasing. To ensure the operational safety of LNG carriers and safeguard the economic interests of stakeholders, including shipowners, a thorough assessment of the navigability of various ice-class LNG carriers along this route is essential. This study collected Arctic ice condition data from 2014 to 2023 and applied the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology to calculate the Risk Index Outcome (RIO) for LNG carriers with No Ice Class, Arc4, and Arc7 ice classifications in Arctic waters. A navigability threshold of 95% RIO ≥ 0 was established to define navigable windows, and critical waters were identified where sections of the route remain in hazardous or risky conditions year-round. The results indicate that for No Ice Class vessels, Arc4 vessels, and Arc7 vessels, the navigable windows for westbound Route 1 and Route 2 under light, normal, and heavy ice conditions range from 70 to 133 days, 70 to 365 days, and 70 to 365 days, respectively, while for eastbound Route 3, the navigable windows range from 0 to 84 days, 0 to 238 days, and 7 to 365 days, respectively. The critical waters affecting the navigability of No Ice Class vessels, Arc4 vessels, and Arc7 vessels are primarily located in the Kara Sea, Laptev Sea and East Siberian Sea. This study, using the POLARIS methodology, provides valuable insights into the navigability of LNG carriers with different ice classes along the NSR, supporting the development and utilization of Arctic energy and shipping routes while offering decision-making support for stakeholders involved in Arctic maritime operations.

An efficient Meta-VSW method for ship behaviors recognition and application - Zhiyuan Cai; Qidong Fan; Lecheng Li; Long Yu; Congbo Li (Ocean Engineering, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Reconstructing high-resolution gridded precipitation data in the southwest China highland canyon area using an improved (MGWR) downscaling method - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Lei Fan; Wei Qin; Lin Ding (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Fraction-dependent variations in cooling efficiency of urban trees across global cities - Wenfeng Zhan; Chunli Wang; Shasha Wang; Long Li; Yingying Ji; Huilin Du; Fan Huang; Sida Jiang; Zihan Liu; Huyan Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Enhanced anti-biochemical fouling properties of the polyacrylonitrile membranes assisted by the d-amino acid surface-modified halloysite nanotubes - Qiao Liu; Nong Xu; Kaiming Li; Qing Wang; Long Fan; Peng Zang; Yinhua Wan (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Magnesium isotope fractionation during magmatic differentiation in the lower continental crust - Ying Wei; Xiao-Long Huang; Qiang Ma; Fan Yang; Peng-Li He (Chemical Geology, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Total Flavonoids of Aurantii Fructus Immaturus Regulate miR-5100 to Improve Constipation by Targeting Fzd2 to Alleviate Calcium Balance and Autophagy in Interstitial Cells of Cajal - Yong Wen; Yu Zhan; Taiyu Chen; Jun Li; Qing Long; Fan Zheng; Shiyu Tang; Xuegui Tang (Molecular Neurobiology, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Totaling river discharge of the third pole from satellite imagery - Jie Xu; Lei Wang; Tandong Yao; Deliang Chen; Gang Wang; Zhaowei Jing; Fan Zhang; Yuyang Wang; Xiuping Li; Yinsheng Zhang; Yuanwei Wang; Tian Zeng; et al. (Remote Sensing of Environment, 2024)

Selective hydroconversion of lignin-derived compounds over a Ni/hydroxyapatite - Yong-Hui Feng; Xiang Bai; Xian-Yong Wei; Yierxiati Dilixiati; Li Li; Qian-Qian Kong; Zhuang Li; Zi-Chun Fan; Ji Zhao; Zhi-Min Zong; Jun-Long Wang (Fuel, 2024)

Protein aggregation caused by pasteurization processing affects the foam performance of liquid egg white - Xiang Fan; Qi Wang; Haobo Jin; Yuanyuan Zhang; Yaqin Yang; Zhe Li; Guofeng Jin; Long Sheng (Food Chemistry, 2024)

Development of a low carbon binder system based on metakaolin: Focus on corrosion inhibitor-intercalated layered double hydroxides - Zhenjiang Gu; Jianbo Xiong; Zhihong Fan; Mengzhu Chen; Jiaqi Li; Long Jiang; Haibing Zheng; Weihua Li (Applied Clay Science, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

Two new cytotoxic diterpenoid alkaloids from Delphinium grandiflorum - Ze-dong Nan; Ying Shang; Chao-fan Deng; Yi-dong Zhu; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Phytochemistry Letters, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Lacustrine shale lithofacies and depositional environment in the paleocene second member of the funing formation, subei basin, China: Insights into shale oil development prospects - Xiaojie Fan; Yangbo Lu; Zhanhong Liu; Yongchao Lu; Jingyu Zhang; Kong Deng; Tao Zhou; Hao Tai; Long Li (Marine and Petroleum Geology, 2024)

C–C bond coupling differences between β-O-4 and 4-O-5 ether bonds over hydrophobic mesoporous Ru/MY-O catalysts: from lignin model compounds to polycyclic alkanes - Zhuang Li; Zi-Chun Fan; Xiang Bai; Xian-Yong Wei; Yierxiati. Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Jun-Long Wang; Xing Fan; Xiao-Yan He; Hai-Xu Zou; et al. (Fuel, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Printed bioinspired piezoelectric nano-hair for ultrahigh sensitive airflow detection - Kai Li; Fan Du; Junyang Fang; Long Sun; Mingzhen Li; Yexin Wang; Chao Wang; Xiaoying Wang; Jinbang Li; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Peroxydisulfate activation and versatility of defective Fe3O4@MOF-808 for enhanced carbon and phosphorus recovery from sludge anaerobic fermentation - Long Chen; Xiangyue Zhang; Jianming Zhu; Helin Fan; Zimu Qin; Jun Li; Haijiao Xie; Hongtao Zhu (Water Research, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Genesis of the Hujiazhuang apatite-rich carbonatite complex in North China and its implication for the REE fertility of the carbonatite system - Long Huang; Xiaochun Li; Jianhui Su; Xi Zeng; Hongrui Fan; Jun Lan; Tingguang Lan; Kuifeng Yang; Fangfang Hu (Journal of Asian Earth Sciences, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Nitazoxanide protects against experimental ulcerative colitis through improving intestinal barrier and inhibiting inflammation - Hu-Tai-Long Zhu; Jing Luo; Yi Peng; Xiao-Fan Cheng; Shang-Ze Wu; Yin-Di Zhao; Le Chang; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Seasonal patterns, fate and ecological risk assessment of pharmaceutical compounds in a wastewater treatment plant with Bacillus bio-reactor treatment - Zi-Feng Zhang; Ying-Ying Fan; Xi-Mei Lu; Xi-ze Min; Wan-Li Ma; Li-Yan Liu; Yi-Fan Li; Wen-Long Li (Journal of Environmental Management, 2024)

Effective catalytic hydroconversion of benzyloxybenzene and oxydibenzene to cyclanes over nickel-supported Y-type zeolite catalyst: Lignite-related model compounds to high-density fuels - Zi-Chun Fan; Zhuang Li; Xiang Bai; Xian-Yong Wei; Yierxiati Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Zhi-Min Zong; Jun-Long Wang (Fuel, 2024)

Contrasting moist heat across local climate zones in heat and non-heat waves: Insights from 29 Chinese metropolises - Sida Jiang; Wenfeng Zhan; Long Li; Chunli Wang; Pan Dong; Shasha Wang; Yingying Ji; Fan Huang; Zihan Liu; Yihan Gao (Building and Environment, 2024)

Metabolomics-based study of chemical compositions in cellulase additives derived from a tobacco-origin Bacillus subtilis and their impact on tobacco sensory attributes - Xiaofeng Chen; Teng Long; Shixin Huang; Yiqiang Chen; Hongliang Lu; Zhenkun Jiang; Cheng Cheng; Jingjing Li; Shanyi Chen; Wei He; Xu Tang; Jianqiang Fan (Archives of Microbiology, 2024)

Species distribution modeling combined with environmental DNA analysis to explore distribution of invasive alien mosquitofish (Gambusia affinis) in China - Xu Han; Jinxiao Chen; Lang Wu; Guo Zhang; Xiaoteng Fan; Tao Yan; Long Zhu; Yongjing Guan; Linjun Zhou; Tingting Hou; Xue Xue; Xiangju Li; et al. (Environmental Science and Pollution Research, 2024)

Phase separation of GRP7 facilitated by FERONIA-mediated phosphorylation inhibits mRNA translation to modulate plant temperature resilience - Fan Xu; Long Wang; Yingbin Li; Junfeng Shi; Dorothee Staiger; Feng Yu (Molecular Plant, 2024)

Sodium caseinate medium promotes the in vitro digestion of starch: An insight into the macromolecular crowding effect - Yu-Long Sun; Yi-Fan Tang; Lei Wang; Mi-Zhuan Li; Zhong-Xiu Chen (Food Chemistry, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Complete genome sequence analysis of Bacillus velezensis A5, a promising biocontrol agent from the Pacific Ocean - Shunhua Ji; Yin Tian; Guangxin Xu; Yiqiang Chen; Jingjing Li; Teng Long; Wei He; Jianqiang Fan; Xixiang Tang (Marine Genomics, 2024)

Intelligent quantitative recognition of sulfide using machine learning-based ratiometric fluorescence probe of metal-organic framework UiO-66-NH2/Ppix - Degui Wang; Long Yu; Xin Li; Yunfei Lu; Chaoqun Niu; Penghui Fan; Houjuan Zhu; Bing Chen; Suhua Wang (Journal of Hazardous Materials, 2024)

Antibiotic resistance genes and heavy metals in landfill: A review - Yan-Jiao Li; Ying Yuan; Wen-Bing Tan; Bei-Dou Xi; Hui Wang; Kun-Long Hui; Jia-Bao Chen; Yi-Fan Zhang; Lian-Feng Wang; Ren-Fei Li (Journal of Hazardous Materials, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Contribution of recycled oceanic crust to the extremely light molybdenum isotopic compositions of mid-ocean ridge basalts from the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Jie Li; Fan Yang; Zhen-Min Ge (Chemical Geology, 2024)

A level IV fugacity-based multimedia model based on steady-state particle/gas partitioning theory and its application to study the spatio-temporal trends of PBDEs in atmosphere of northeast China - Meng Qin; Wan-Li Ma; Pu-Fei Yang; Wen-Long Li; Lei Wang; Li-Li Shi; Li Li; Yi-Fan Li (Science of The Total Environment, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Role of crustal radiogenic heating in ultra-high temperature metamorphism of the Greater Himalayan Crystalline complex: Phase equilibrium and numerical modelling - Yin-Long Fan; Li-Fei Zhang; Yang Wang; Zhong-Hai Li (Gondwana Research, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Experimental study on the flow characteristics of 7-pin hexagonal bundle assembly with grid spacers - Rongjie Li; Dajun Fan; Minghan He; Yang Liu; Qianwan Shi; Yanze Tang; Wangsheng Tian; Deliang Fan; Long Gu (Annals of Nuclear Energy, 2023)

Identification of Bone Metastatic and Prognostic Alternative Splicing Signatures in Prostate Adenocarcinoma - Jiwen Zhu; Jiayao Zhang; Peng Hu; Mingxiang Fan; Dianwen Song; Huabin Yin; Penghui Yan; Shuyuan Xian; Zhenyu Li; Juanru Guo; Chunling Long; Runping Xu; et al. (Biochemical Genetics, 2023)
As the most common nonepithelial malignancy, prostate adenocarcinoma (PRAD) is the fifth chief cause of cancer mortality in men. Distant metastasis often occurs in advanced PRAD and most patients are dying from it. However, the mechanism of PRAD progression and metastasis is still unclear. It’s widely reported that more than 94% of genes are selectively splicing in humans and many isoforms are particularly related with cancer progression and metastasis. Spliceosome mutations occur in a mutually exclusive manner in breast cancer, and different components of spliceosomes are targets of somatic mutations in different types of breast cancer. Existing evidence strongly supports the key role of alternative splicing in breast cancer biology, and innovative tools are being developed to use splicing events for diagnostic and therapeutic purposes. In order to identify if the PRAD metastasis is associated with alternative splicing events (ASEs), the RNA sequencing data and ASEs data of 500 PRAD patients were retrieved from The Cancer Genome Atlas (TCGA) and TCGASpliceSeq databases. By Lasso regression, five genes were screened to construct the prediction model, with a good reliability by ROC curve. Additionally, results in both univariate and multivariate Cox regression analysis confirmed the well prognosis efficacy of the prediction model (both P P P

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The number and position of unsaturated bonds in aliphatic aldehydes affect the cysteine-glucose Maillard reaction: Formation mechanism and comparison of volatile compounds - Wenbin Du; Yutang Wang; Qinghong Yan; Shuang Bai; Yatao Huang; Long Li; Yuwen Mu; Ashbala Shakoor; Bei Fan; Fengzhong Wang (Food Research International, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Different B Mo isotopic fractionation processes controlled by redox conditions in the subduction zone - Yang Yu; Xiao-Long Huang; Yu-Ming Lai; Jie Li; Yi-Gang Xu; Sun-Lin Chung; Iwan Setiawan; Fan Yang (Chemical Geology, 2023)

Intracontinental lithospheric delamination: Constraints from imaging the mantle transition zone beneath the southwestern part of the Sichuan Basin - Fan Yang; Juan Li; Sidan Chen; Yun Chen; Long Li; Yinshuang Ai (Science China Earth Sciences, 2023)

Dynamic valuation of the provisioning services of marine fisheries ecosystem based on BeiDou VMS data: A case study of TACs project for Acetes chinensis in the Yellow Sea - Guodong Li; Dongjia Li; Ying Xiong; Xiaming Zhong; Jinjin Shi; Hushun Zhang; Dade Song; Fan Yang; Zhongjie Kang; Xiaorui Wu; Shuyan Wang; Long Liang (Ocean & Coastal Management, 2023)

Divergent urbanization-induced impacts on global surface urban heat island trends since 1980s - Long Li; Wenfeng Zhan; Leiqiu Hu; TC Chakraborty; Zhihua Wang; Peng Fu; Dazhong Wang; Weilin Liao; Fan Huang; Huyan Fu; Jiufeng Li; Zihan Liu; et al. (Remote Sensing of Environment, 2023)

Pilot-scale study on an advanced Fe-Cu process for refractory wastewater pretreatment - Jin-Hong Fan; Zhen-long Yao; De-li Wu; Xia Liu; Lu-ming Ma (Journal of Hazardous Materials, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Regulation of soil water and nitrate by optimizing nitrogen fertilization and the addition of manure based on precipitation: An 8-year field record - Wenguang Li; Long Ma; Fan Shi; Shuting Wang; Jiarui Zhao; Wei Zheng; Zhijun Li; Ziyan Li; Bingnian Zhai (Agriculture, Ecosystems & Environment, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Recyling manganese-rich electrolytic residues: a review - Fan Wang; Guangcheng Long; Kunlin Ma; Xiaohui Zeng; Zhuo Tang; Rongzhen Dong; Jionghuang He; Minghui Shangguan; Qingchun Hu; Rock Keey Liew; Yang Li; John Zhou (Environmental Chemistry Letters, 2023)

miRNAs contributing to the repair of tendon injury - Kexin Lyu; Xinyue Liu; Tianzhu Liu; Jingwei Lu; Li Jiang; Yixuan Chen; Longhai Long; Xiaoqiang Wang; Houyin Shi; Fan Wang; Sen Li (Cell and Tissue Research, 2023)
Tendon injury is one of the most common disorders of the musculoskeletal system, with a higher likelihood of occurrence in elderly individuals and athletes. In posthealing tendons, two undesirable consequences, tissue fibrosis and a reduction in mechanical properties, usually occur, resulting in an increased probability of rerupture or reinjury; thus, it is necessary to propose an appropriate treatment. Currently, most methods do not sufficiently modulate the tendon healing process and restore the function and structure of the injured tendon to those of a normal tendon, since there is still inadequate information about the effects of multiple cellular and other relevant signaling pathways on tendon healing and how the expression of their components is regulated. microRNAs are vital targets for promoting tendon repair and can modulate the expression of biological components in signaling pathways involved in various physiological and pathological responses. miRNAs are a type of noncoding ribonucleic acid essential for regulating processes such as cell proliferation, differentiation, migration and apoptosis; inflammatory responses; vascularization; fibrosis; and tissue repair. This article focuses on the biogenesis response of miRNAs while presenting their mechanisms in tendon healing with perspectives and suggestions.

Spatial distribution and temporal trend of organochlorine pesticides in Chinese surface soil - Shuai Hao; Wen-Long Li; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma; Yi-Fan Li (Environmental Science and Pollution Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

A comparative study of different iron minerals on phosphorus capture from municipal wastewater and subsequent recovery as vivianite through acidogenic fermentation - Shi-Xu Wang; Yun-Xin Huang; Hao Wang; Yao-Yao Lu; Wen-Long He; Jing Li; Nian-Si Fan; Bao-Cheng Huang; Ren-Cun Jin (Chemical Engineering Journal, 2023)

Metformin Alleviates Delayed Hydrocephalus after Intraventricular Hemorrhage by Inhibiting Inflammation and Fibrosis - Yi Cao; Chang Liu; Gaowei Li; Weina Gao; Hui Tang; Shuanmin Fan; Xin Tang; Long Zhao; Haoxiang Wang; Aijun Peng; Chao You; Aiping Tong; et al. (Translational Stroke Research, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Effects of cadmium on transcription, physiology, and ultrastructure of two tobacco cultivars - Zhiguo Liu; Xiuzhe Wu; Lei Hou; Shengzhe Ji; Yao Zhang; Weiru Fan; Tong Li; Li Zhang; Peng Liu; Long Yang (Science of The Total Environment, 2023)

Fabrication of an alginate-based ZhiNengCong gel showed an enhanced antiviral and plant growth promoting functions - Long Jiang; Qin Wang; Shuai Zhang; Changyun Liu; Ke Wang; Fengwei Li; Xiaoyan Wang; Weina Liu; Xiaozhou Ma; Guangjin Fan; Tiancai Chen; Yabo Jin; et al. (Pesticide Biochemistry and Physiology, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Effect of different vegetation restoration on soil organic carbon dynamics and fractions in the Rainy Zone of Western China - Fan Yang; Yujian Zhong; Guangzhong Han; Xiuzhi Li; Li Luo; Xiaomin Cai; Xinyu Long; Tangli Li; Laiming Huang (Journal of Environmental Management, 2023)

Biomass types of nitrate-reducing denitrifiers to differentiate the hybrid community allocation of partial denitrification (PD) and anammox: IFAS vs MBBR - Lifang Yu; Yiting Wang; Xin Tian; Ye Fan; Yexing Liu; Jiayi Yang; Long Li (Chemical Engineering Journal, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Seasonal variations of airborne phthalates and novel non-phthalate plasticizers in a test residence in cold regions: Effects of temperature, humidity, total suspended particulate matter, and sources - Chun-Yan Huo; Wen-Long Li; Li-Yan Liu; Yu Sun; Jia-Qi Guo; Liang Wang; Hayley Hung; Yi-Fan Li (Science of The Total Environment, 2023)

Competition between biogeochemical drivers and land-cover changes determines urban greening or browning - Long Li; Wenfeng Zhan; Weimin Ju; Josep Peñuelas; Zaichun Zhu; Shushi Peng; Xiaolin Zhu; Zihan Liu; Yuyu Zhou; Jiufeng Li; Jiameng Lai; Fan Huang; et al. (Remote Sensing of Environment, 2023)

Catalytic activation of formic acid using Pd nanocluster decorated graphitic carbon nitride for diclofenac reductive hydrodechlorination - Feng Shao; Yixuan Gao; Wenhui Xu; Fengbin Sun; Long Chen; Fan Li; Wen Liu (Journal of Hazardous Materials, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Response of Soil Bacteria of Dicranopteris dichotoma Populations to Vegetation Restoration in Red Soil Region of China - Qi-yan Li; Chen-lu Zhu; Jun-bao Yu; Xin-yi Wu; Si-qi Huang; Fan Yang; Mulualem Tigabu; Xiao-long Hou (Journal of Soil Science and Plant Nutrition, 2023)

Airflow characteristics of rotorcraft plant protection UAV operating in rice fields - Gangao Fan; Zhijie Liu; Yijuan Qin; Bo Long; Huifen Li; Jiyu Li (Biosystems Engineering, 2023)

Different reaction mechanisms of SO4•− and •OH with organic compound interpreted at molecular orbital level in Co(II)/peroxymonosulfate catalytic activation system - Huixuan Zhang; Chenghan Xie; Long Chen; Jun Duan; Fan Li; Wen Liu (Water Research, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Bioactive components and beneficial bioactivities of flowers, stems, leaves of Lonicera japonica Thunberg: A review - Yuke Li; Long Xie; Kai Liu; Xiaofang Li; Fan Xie (Biochemical Systematics and Ecology, 2023)

Default mode network mechanisms of repeated transcranial magnetic stimulation in heroin addiction - Long Jin; Menghui Yuan; Wei Zhang; Lei Wang; Jiajie Chen; Fan Wang; Jia Zhu; Tao Liu; Yixin Wei; Yunbo Li; Wei Wang; Qiang Li; et al. (Brain Imaging and Behavior, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Cationic molecular probes based on aggregation-induced emission for fluorescent sensing and super-resolution imaging of insulin fibrosis - Li-Jun Mei; Cheng Fan; Chu-Ran Xu; Qi Yu; Chong Li; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Groundwater Quality Evaluation and Analysis Technology Based on AHP-EWM-GRA and Its Application - Menghua Li; Bo Li; Jingyan Chu; Huang Wu; Zhicheng Yang; Juan Fan; Lei Yang; Pu Liu; Jie Long (Water, Air, & Soil Pollution, 2023)

Water consumption prediction and influencing factor analysis based on PCA-BP neural network in karst regions: a case study of Guizhou Province - Zhicheng Yang; Bo Li; Huang Wu; MengHua Li; Juan Fan; Mengyu Chen; Jie Long (Environmental Science and Pollution Research, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

Potential antibacterial and anti-biofilm effects of Anoectochilus roxburghii rhizome cultures - Ming-Zhi Fan; Xiao-Long Jiang; Xuan-Chun Piao; Xue-Feng Li; Mei-Yu Jin; Mei-Lan Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Genome-wide association study of SARS-CoV-2 infection in Chinese population - Jie Fan; Quan-Xin Long; Ji-Hua Ren; Hao Chen; Meng-Meng Li; Zheng Cheng; Juan Chen; Li Zhou; Ai-Long Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

Identification and characterization of stress responsive homeodomain leucine zipper transcription factors in Medicago truncatula - Xiao Li; Yiyao Hou; Fan Zhang; Mingna Li; Fengyan Yi; Junmei Kang; Qingchuan Yang; Ruicai Long (Molecular Biology Reports, 2022)

Noninvasive oral cancer screening based on local residual adaptation network using optical coherence tomography - Wei Yuan; Long Cheng; Jinsuo Yang; Boya Yin; Xingyu Fan; Jing Yang; Sen Li; Jianjun Zhong; Xin Huang (Medical & Biological Engineering & Computing, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Xiangyu Long; Rong Wan; Zengguang Li; Dong Wang; Pengbo Song; Fan Zhang (Frontiers in Marine Science, 2022)
A fishery-independent survey can provide detailed information for fishery assessment and management. However, the sampling design for the survey on ichthyoplankton in the estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with the Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from the fishery-independent survey in 2019–2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB), and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between the North Branch and South Branch but between river and sea. No less than two stratifications in the South Branch could also get better performance. The sample sizes of 45–55 were considered as the cost-efficient range. Compared to other monitoring programs, monitoring ichthyoplankton in the estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in the estuary area.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

The role of earthquake-induced landslides in erosion and weathering from active mountain ranges: Progress and perspectives - Zhangdong Jin; Robert G. Hilton; A. Joshua West; Gen K. Li; Fei Zhang; Jin Wang; Gaojun Li; Xuanmei Fan; Meng-Long Hsieh (Science China Earth Sciences, 2021)

Fate processes of Parabens, Triclocarban and Triclosan during wastewater treatment: assessment via field measurements and model simulations - Zi-Feng Zhang; Lu Wang; Xianming Zhang; Xue Zhang; Yi-Fan Li; Anatoly Nikolaev; Wen-Long Li (Environmental Science and Pollution Research, 2021)

Deep Learning Convolutional Neural Network Applying for the Arctic Acoustic Tomography Current Inversion Accuracy Improvement - Kangkang Jin; Jian Xu; Zichen Wang; Can Lu; Long Fan; Zhongzheng Li; Jiaxin Zhou (Journal of Marine Science and Engineering, 2021)
Warm current has a strong impact on the melting of sea ice, so clarifying the current features plays a very important role in the Arctic sea ice coverage forecasting study field. Currently, Arctic acoustic tomography is the only feasible method for the large-range current measurement under the Arctic sea ice. Furthermore, affected by the high latitudes Coriolis force, small-scale variability greatly affects the accuracy of Arctic acoustic tomography. However, small-scale variability could not be measured by empirical parameters and resolved by Regularized Least Squares (RLS) in the inverse problem of Arctic acoustic tomography. In this paper, the convolutional neural network (CNN) is proposed to enhance the prediction accuracy in the Arctic, and especially, Gaussian noise is added to reflect the disturbance of the Arctic environment. First, we use the finite element method to build the background ocean model. Then, the deep learning CNN method constructs the non-linear mapping relationship between the acoustic data and the corresponding flow velocity. Finally, the simulation result shows that the deep learning convolutional neural network method being applied to Arctic acoustic tomography could achieve 45.87% accurate improvement than the common RLS method in the current inversion.

High-density mapping for gray leaf spot resistance using two related tropical maize recombinant inbred line populations - Long Chen; Li Liu; Ziwei Li; Yudong Zhang; Manjit S. Kang; Yunyue Wang; Xingming Fan (Molecular Biology Reports, 2021)

Distribution characteristics and main influencing factors of selenium in surface soil of natural selenium-rich area: a case study in Langao County, China - Litao Hao; Jiandong Zhang; Shixi Zhang; Sumin Ma; Bo Li; Jie Long; Jingsen Fan; Kunli Luo (Environmental Geochemistry and Health, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Responses of phytoplankton functional groups to environmental factors in the Pearl River, South China - Shengxing Long; Ting Zhang; Jingjing Fan; Can Li; Kangning Xiong (Environmental Science and Pollution Research, 2020)

Cortical morphometry alterations in brain regions involved in emotional, motor-control and self-referential processing in patients with functional constipation - Chunxin Hu; Li Liu; Lei Liu; Junwang Zhang; Yang Hu; Wenchao Zhang; Yueyan Ding; Yuanyuan Wang; Zhida Zhang; Karen M. von Deneen; Long Qian; Huaning Wang; et al. (Brain Imaging and Behavior, 2020)

Molecular cloning and expression analysis of the transcription factor CobHLH40 from Cornus officinalis on the basis of de novo transcriptome sequencing - Dianyun Hou; Wenbin Wang; Mengmeng Yang; Zhihong Li; Jingya Xu; Long Wang; Zhenjie Fan; Yaoyao Wang (Plant Biotechnology Reports, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)

Correction to: The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Seismic design and behavior of self-centering energy dissipation braced steel frame - Long-He Xu; Yu-Sheng Sun; Xiao-Wei Fan; Zhong-Xian Li (Bulletin of Earthquake Engineering, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Effects of metaxenia on the carbohydrate and mogroside content and related enzyme activities in Siraitia grosvenorii fruit - Zhi-gang Yan; Dong Xiao; Yong-li Xu; Jing Ma; Fan Liu; Long-hua Bai; Xiao-jun Ma (Acta Physiologiae Plantarum, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Magnetic nanoparticles based cancer therapy: current status and applications - Huan Zhang; Xiao Li Liu; Yi Fan Zhang; Fei Gao; Ga Long Li; Yuan He; Ming Li Peng; Hai Ming Fan (Science China Life Sciences, 2018)

Soybean and cottonseed meals are good candidates for fishmeal replacement in the diet of juvenile Macrobrachium nipponense - Yu-Juan Huang; Nan-Nan Zhang; Wu-Jiang Fan; Yan-Yan Cui; Samwel Mchele Limbu; Fang Qiao; Yun-Long Zhao; Li-Qiao Chen; Zhen-Yu Du; Dong-Liang Li (Aquaculture International, 2018)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

C-Reactive Protein Gene Contributes to the Genetic Susceptibility of Hemorrhagic Stroke in Men: a Case-Control Study in Chinese Han Population - Yong Xue; Long Zhang; Yao Fan; Qianhui Li; Yuzhang Jiang; Chong Shen (Journal of Molecular Neuroscience, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Molecular cloning and functional analysis of the drought tolerance gene MsHSP70 from alfalfa (Medicago sativa L.) - Zhenyi Li; Ruicai Long; Tiejun Zhang; Zhen Wang; Fan Zhang; Qingchuan Yang; Junmei Kang; Yan Sun (Journal of Plant Research, 2017)

New isocoumarin and stilbenoid derivatives from the tubers of Sparganium stoloniferum (Buch.-Ham.) - Da-Wei Wu; Qiao-Li Liang; Xiao-Long Zhang; Zheng Jiang; Xiu-He Fan; Wei Yue; Qi-Nan Wu (Natural Product Research, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Genome-wide profiling of genetic variation in Agrobacterium-transformed rice plants - Wen-xu Li; San-ling Wu; Yan-hua Liu; Gu-lei Jin; Hai-jun Zhao; Long-jiang Fan; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Manufacturer identification and storage time determination of “Dong’e Ejiao” using near infrared spectroscopy and chemometrics - Wen-long Li; Hai-fan Han; Lu Zhang; Yan Zhang; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2016)

A Novel Chromone Schiff-Base Fluorescent Chemosensor for Cd(II) Based on C=N Isomerization - Jun Yan; Long Fan; Jing-can Qin; Chao-rui Li; Zheng-yin Yang (Journal of Fluorescence, 2016)

High pH-induced flocculation of marine Chlorella sp. for biofuel production - Fangfang Yang; Wenzhou Xiang; Jiewei Fan; Hualian Wu; Tao Li; Lijuan Long (Journal of Applied Phycology, 2016)

Bacterioplankton community analysis in tilapia ponds by Illumina high-throughput sequencing - Li Min Fan; Kamira Barry; Geng Dong Hu; Shun long Meng; Chao Song; Wei Wu; Jia Zhang Chen; Pao Xu (World Journal of Microbiology and Biotechnology, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Physiological characterization of maize tolerance to low dose of aluminum, highlighted by promoted leaf growth - Liang Wang; Xian-Wei Fan; Jian-Long Pan; Zhang-Bao Huang; You-Zhi Li (Planta, 2015)

Isolation and functional characterization of salt-stress induced RCI2-like genes from Medicago sativa and Medicago truncatula - Ruicai Long; Fan Zhang; Zhenyi Li; Mingna Li; Lili Cong; Junmei Kang; Tiejun Zhang; Zhongxiang Zhao; Yan Sun; Qingchuan Yang (Journal of Plant Research, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

Integration of metal chemical forms and subcellular partitioning to understand metal toxicity in two lettuce (Lactuca sativa L.) cultivars - Cheng-Cheng Li; Fei Dang; Long Cang; Chui-Fan Zhou; Dong-Mei Zhou (Plant and Soil, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Phylogeography of Sophora davidii (Leguminosae) across the ‘Tanaka‐Kaiyong Line’, an important phytogeographic boundary in Southwest China - Deng Mei Fan; Ji Pei Yue; Ze Long Nie; Zhi Min Li; Hans Peter Comes; Hang Sun (Molecular Ecology, 2013)
The ‘Tanaka‐Kaiyong Line’ ( TKL ) is a major phytogeographic boundary in Southwest China, separating East Asia's Sino‐Himalayan and Sino‐Japanese Floras. However, little is known about the importance of this boundary in promoting intraspecific phylogeographic subdivision and divergence. Using chloroplast (cp DNA ) and nuclear‐intron ( nDNA ) sequence data, we reconstructed the population history of Sophora davidii , a drought‐tolerant riparian shrub widely distributed on either side of the TKL . Specifically, we aimed at testing two long‐standing explanations for possible vicariant events across the TKL: (i) Late Pliocene ( c . 3 Ma) geological uplift of the eastern Qinghai‐Tibetan Plateau (QTP) or (ii) a sharp environmental gradient associated with the establishment of different monsoon regimes on either side of the TKL during the (Late) Pleistocene. Our genealogical analyses detected a major west–east split in cpDNA, geographically largely consistent with the TKL, and dated to c . 1.28 Ma (95% HPD: 0.21–2.96 Ma), hence postdating the latest phase of eastern QTP uplift. Furthermore, integrating cpDNA phylogeographic patterns with mismatch analyses, we found multiple refugial isolation and long‐term demographic stability of populations in the west (Hengduan Mountain Range) compared with extensive range expansions in the east, possibly during the last glacial period(s) and followed by differentiation into regional sublineages (southeast: Yunnan‐Guizhou Plateau vs. northeast: Qinling Mts./Loess Plateau). Although nuclear differentiation was less marked, the geographical pattern of nDNA haplotypes provided some further indication of the species' eastward expansion, possibly from source populations located just east of the TKL (lower Jinshajiang region). Overall, the present data reject the geological (tectonic) explanation for the TKL and, instead, provide supportive evidence for its role as a climatically driven barrier to present‐day plant dispersal. In addition, our study highlights changing temperatures and vegetation types during the last glacial period(s), along with aspects of regional topography, to be important determinants of the glacial eastward expansion of S. davidii . In consequence, our study lends support to a ‘glacial out‐of‐Hengduan Mts’. hypothesis for the xerophytic‐riparian flora of Southwest China, which in turn is inconsistent with the traditional view of the TKL as a ‘classical’ vicariant‐biogeographic boundary.

Diversity arrays technology (DArT) for studying the genetic polymorphism of flue-cured tobacco (Nicotiana tabacum) - Xiu-ping Lu; Bing-guang Xiao; Yong-ping Li; Yi-jie Gui; Yu Wang; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Development and application of a set of breeder-friendly SNP markers for genetic analyses and molecular breeding of rice (Oryza sativa L.) - Haodong Chen; Hang He; Yanjiao Zou; Wei Chen; Renbo Yu; Xia Liu; Yang Yang; Yong-Ming Gao; Jian-Long Xu; Liu-Min Fan; Yi Li; Zhi-Kang Li; et al. (Theoretical and Applied Genetics, 2011)

Cooperation of deregulated Notch signaling and Ras pathway in human hepatocarcinogenesis - Renhua Fan; Pingsheng Chen; Di Zhao; Jing long Tong; Jing Li; Feng Liu (Journal of Molecular Histology, 2011)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Nitrogen Fixation of Faba Bean (Vicia faba L.) Interacting with a Non-legume in Two Contrasting Intercropping Systems - Fenliang Fan; Fusuo Zhang; Yana Song; Jianhao Sun; Xingguo Bao; Tianwen Guo; Long Li (Plant and Soil, 2006)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)